From #endthestigma to #realman: Stigma-Challenging Social Media Responses to NBA Players' Mental Health Disclosures. (1st September 2020) - Parrott, Scott; Billings, Andrew C.; Hakim, Samuel D.; Gentile, Patrick
Abstract : A number of professional athletes have used social media to disclose personal experience with mental illness, including NBA All-Stars DeMar DeRozan and Kevin Love in 2018. The disclosures could serve to challenge the stigmatization of mental illness, given the positive social standing of professional athletes and the potential power of parasocial relationships in health promotion and behavior. The present study quantitatively examined 3, 366 fan responses to the mental health disclosures of both athletes, unpacking the extent to which fan commentary perpetuated or challenged the stigmatization of depression and anxiety. Fans provided overwhelmingly positive response to the athletes' mental health disclosures, creating a normative environment in which disclosure translated into acceptance rather than rejection. While more frequently offering messages of advice and strength to DeRozan, fans were more likely to offer messages of encouragement and personal experiences with mental illness to Love.